Wearable and wireless sEMG acquisition system based on the Internet of Medical Things - Manuela Gomez-Correa; David Cruz-Ortiz; Mariana Ballesteros (Sensing and Bio-Sensing Research, 2025)
The use and development of wearable systems, including the Internet of Things, have become very relevant in recent years. This type of technology has gained popularity in biomedical applications thanks to its advantages in remote patient monitoring and rehabilitation. The aim of the above is to generate greater access to health services, create personalized systems adapted to the needs of patients, and reduce the necessity of having specialized personnel constantly available while evaluating users. Therefore, the present work developed a portable and wireless surface electromyography (sEMG) system based on the Internet of Medical Things, named MUSS, for Muscle Sensing System. This system has eight wireless modules for biosignal recording, online acquisition, and sEMG signal processing. The system presents an innovative circuit that uses Wi-Fi communication for the online adjustment of sEMG parameters, such as gain, signal offset, and the implementation of digital filters to perform tests based on the application’s needs. Finally, the developed software allows the connection to the Cloud for remote control, information exchange between specialized personnel, and Cloud storage for greater accessibility. The system comparison with different commercial devices and a clinical device demonstrated the usability and advantages of the device developed, considering features such as signal-to-noise ratio, frequency peaks, energy, among others.